Toxicity evaluation of curcumin analogue on zebrafish - Tan, Hong Wei (2015)
Non-steroidal anti-inﬂammatory drugs (NSAIDs) are among the most broadly prescribed medications in the world. But, NSAIDs confer side effects towards the gastrointestinal(GI) system.In Malaysia, the usage of one of the NSAIDs,celecoxib, a Cyclooxygenase-2 (COX-2) inhibitors, had increased by two fold from 2006 to 2007. Curcumin analogues are of great interest in pharmacological research due to its advantages compared with pure curcumin. Curcumin analogues are proposed to be used as an alternative curative drugs for the treatment of certain ailments such as inflammatory diseases.Recently, zebrafish has emerge as a toxicology test model organism for the research of vertebrae genetics and developmental biology. The aim of this research is to determine the effect of curcumin analogue (MS65) on zebrafish embryos survivability and heart beat, zebrafish embryos development, and the kidney and intestine of adult zebrafish. The estimated LC₅₀ of curcumin analogue were 12.5µM for embryos and larvae. Histological analysis of the MS65 treated kidney of adult zebrafish showed low levels of necrosis while eroded villi was associated with MS65 treated zebrafish intestine. Meanwhile, zebrafish larvae incubated with MS65 developed yolk sac edema. Hence, the low toxicity shown by curcumin analogue (MS65) on zebrafish embryos and larvae led to the proposal of curcumin analogue (MS65) to be developed as an anti-inflammatory drugs. Further pre-clinical and clinical toxicity studies have to be done before MS65 can be developed as a new drug.